A theoretical study on the metal contacts of monolayer gallium nitride (GaN). (September 2018) - Sun, Rui; Yang, Guofeng; Wang, Fuxue; Chu, Guangyong; Lu, Naiyan; Shen, Xiaowen
Abstract: Low-Schottky barrier height (SBH) metal contacts to 2D materials is indispensable for achieving high performance in atomic layer 2D materials channel based optoelectronic devices. In this study, we systematically investigate the detailed face contact properties of monolayer (ML) hexagonal gallium nitride (GaN) with six different commonly used metals (Au, Ag, Pd, Pt, Ti, and Ni) in field-effect transistors (FETs) utilizing the first principles electronic structure calculations based on density functional theory (DFT). It is found that no tunnelling barriers (TB) exist in all the ML GaN-metal face contact systems by calculating and analyzing the average effective potentials (Veff). Moreover, ML GaN undergoes a vanishing of Schottky barriers in the vertical interfaces by analyzing the binding energy, electron localization function (ELF), and projected state density (PDOS) of six contact combinations. In terms of the energy band calculation, ML GaN forms n-type Schottky contacts with Au, Pd, Pt and Ti electrodes, and an n-type ohmic contacts with Ag electrode, while a p-type ohmic contact with Ni electrode is obtained in the lateral interfaces. The results would provide an insight into the ML GaN-metal interfaces, and be beneficial for developing low dimensional GaN-based devices with high performance.